Studying the Effects of Granulocyte-Macrophage Colony-Stimulating Factor on Fetal Lung Macrophages During the Perinatal Period Using the Mouse Model - Cheah, Fook-Choe; Presicce, Pietro; Tan, Tian-Lee; Carey, Brenna C.; Kallapur, Suhas G. (Frontiers in Pediatrics, 2021)
Background: Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a pro-inflammatory cytokine that is increased in the amniotic fluid in chorioamnionitis and elevated in the fetal lung with endotoxin exposure. Although GM-CSF has a pivotal role in fetal lung development, it stimulates pulmonary macrophages and is associated with the development of bronchopulmonary dysplasia (BPD). How antenatal GM-CSF results in recruitment of lung macrophage leading to BPD needs further elucidation. Hence, we used a transgenic and knock-out mouse model to study the effects of GM-CSF focusing on the fetal lung macrophage. Methods: Using bitransgenic (BTg) mice that conditionally over-expressed pulmonary GM-CSF after doxycycline treatment, and GM-CSF knock-out (KO) mice with no GM-CSF expression, we compared the ontogeny and immunophenotype of lung macrophages in BTg, KO and control mice at various prenatal and postnatal time points using flow cytometry and immunohistology. Results: During fetal life, compared to controls, BTg mice over-expressing pulmonary GM-CSF had increased numbers of lung macrophages that were CD68+ and these were primarily located in the interstitium rather than alveolar spaces. The lung macrophages that accumulated were predominantly CD11b+F4/80+ indicating immature macrophages. Conversely, lung macrophages although markedly reduced, were still present in GM-CSF KO mice. Conclusion: Increased exposure to GM-CSF antenatally, resulted in accumulation of immature macrophages in the fetal lung interstitium. Absence of GM-CSF did not abrogate but delayed the transitioning of interstitial macrophages. Together, these results suggest that other perinatal factors may be involved in modulating the maturation of alveolar macrophages in the developing fetal lung.